2016
DOI: 10.1007/s40119-016-0066-2
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review on the Cost-Effectiveness of Apixaban for Stroke Prevention in Non-valvular Atrial Fibrillation

Abstract: IntroductionEconomic evaluations are becoming increasingly important due to limitations in economic resources, the expense of many new treatments, the need to allocate health spending as effectively as possible, and the need to inform decision makers. Based on the data from the apixaban studies (ARISTOTLE and AVERROES), several economic evaluations have been performed in various countries to demonstrate the efficacy of apixaban versus warfarin and aspirin or other new oral anticoagulants (NOACs) for preventing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Furthermore, despite the discrepancy in patient cost because of the requirement for monthly repeat prescriptions, recent studies have suggested that DOAC therapy and in particular apixaban are in general cost-effective to the health system when compared to warfarin for stroke prevention in patients with non-valvular AF. [19][20][21] After switching from warfarin to DOACs, clinically relevant non-major bleeding was the most common side effect that necessitated further management. This finding is consistent with the reports of menorrhagia in woman of childbearing age prescribed DOACs but with appropriate intervention, the DOAC can generally be continued for effective thrombosis risk PLOS ONE reduction.…”
Section: Plos Onementioning
confidence: 99%
“…Furthermore, despite the discrepancy in patient cost because of the requirement for monthly repeat prescriptions, recent studies have suggested that DOAC therapy and in particular apixaban are in general cost-effective to the health system when compared to warfarin for stroke prevention in patients with non-valvular AF. [19][20][21] After switching from warfarin to DOACs, clinically relevant non-major bleeding was the most common side effect that necessitated further management. This finding is consistent with the reports of menorrhagia in woman of childbearing age prescribed DOACs but with appropriate intervention, the DOAC can generally be continued for effective thrombosis risk PLOS ONE reduction.…”
Section: Plos Onementioning
confidence: 99%
“…The efficiency of these drugs has been assessed in different settings and with different comparators. These studies include cost-effectiveness analyses of apixaban versus warfarin, acenocoumarol, ASA, dabigatran and rivaroxaban [ 13 ] and, most recently, a cost-utility analysis versus edoxaban in the UK [ 14 ]. Evaluations specifically for the Spanish setting include those for apixaban versus acenocoumarol [ 15 ], apixaban versus dabigatran [ 16 ] and apixaban versus rivaroxaban [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The economic value of apixaban has been demonstrated in an independent cost-effectiveness analysis conducted in UK and based on the data from a network meta-analysis of 23 RCTs [12], which showed that apixaban has a slightly higher expected quality-adjusted life expectancy (QALYs: 5.49 vs. 5.45 of rivaroxaban, 5.42 of dabigatran 150 mg, and 5.41 of edoxaban 60 mg) and the highest probability of being the most cost-effective first-line therapy for AF (close to 60% for willingness to pay thresholds of £ 20,000-30,000). In a systematic review on the cost-effectiveness of apixaban for stroke prevention, which included 23 costeffectiveness studies from 14 countries, apixaban appears to be more cost-effective than warfarin and other DOACs [27].…”
Section: Discussionmentioning
confidence: 99%